Safety and Efficacy of Bis-Glyceryl Ascorbate as Prophylaxis for Hand-Foot Skin Reaction: A Single-Arm, Open-Label Phase I/II Study (DGA Study). (14th March 2022) - Yamamoto, Kazuhiro; Nishiyama, Satoshi; Kunisada, Makoto; Iida, Masashi; Ito, Takahiro; Ioroi, Takeshi; Makimoto, Hiroo; Omura, Tomohiro; Harada, Kenichi; Fujisawa, Masato; Nishigori, Chikako; Yano, Ikuko
Abstract : Hand-foot skin reaction induced by multiple tyrosine kinase inhibitors is a serious side effect that can cause treatment interruption or decreased dosing. This study was conducted to evaluate the safety and efficacy of a bis-glyceryl ascorbate-containing cream for the prevention of sunitinib-induced hand-foot skin reaction. Abstract: Background: Hand-foot skin reaction (HFSR) induced by multiple tyrosine kinase inhibitors (TKIs) is a serious side effect that can cause treatment interruption or decreased dosing. This study was conducted to evaluate the safety and efficacy of bis-glyceryl ascorbate (Amitose bis(di)-glyceryl ascorbate [DGA])-containing cream (DGA cream) for the prevention of sunitinib-induced HFSR. Methods: A single-arm, open-label phase I/II study was conducted, targeting patients with metastatic renal cell carcinoma (mRCC) who were receiving sunitinib therapy with a schedule of 2 weeks on/1 week off. The participants applied DGA cream to both palmar and plantar surfaces in combination with a moisturizing agent as standard-of-care prophylaxis during two sunitinib treatment cycles (6 weeks). The primary endpoint in phase I was safety defined as dermatological abnormalities and it was determined in the first five participants. The primary endpoint in phase II was efficacy defined as development of grade 1 or higher HFSR defined by Common Terminology Criteria for Adverse Events within 6 weeks and it was determined on a full analysis set (FAS) defined as the population including all participants who used DGA cream once in the study duration. Efficacy in the per protocol set (PPS) defined as the population excluding seven patients whose study treatment was interrupted was evaluated as a secondary endpoint. Results: Twenty-four patients were enrolled as a FAS. No dermatological abnormalities occurred in the first 5 patients enrolled in the phase I study. Three patients developed HFSR (grade 1: n = 2, grade 2: n = 1) in the observation period. The HFSR incidence rate was 12.5% (3/24; 95% confidence interval [CI]: 2.7%-32.4%) in the FAS, which was significantly lower than the incidence rate predefined as a threshold of 33.3% by a previous report from our hospital ( P = .030). The incidence rate in the 17 patients of the PPS was 17.6% (3/17; 95%CI: 3.8%-43.4%). Conclusion: DGA cream may be safe and effective in the prophylaxis of HFSR in mRCC patients who receive sunitinib therapy (Trial ID: jRCTs051180051).